Client satisfaction regarding health care services provided by Auxiliary Nurse Midwives in North India - Anup Dewanand Salve; Kavita; Amarjeet Singh; Sushma Kumari Saini (Wolters Kluwer Medknow Publications, 2017)
Introduction: In recent years more responsibility have been added to the work of Auxiliary Nurse Midwives (ANMs) affecting the satisfaction of the users. So need was felt to conduct a study on the satisfaction of clients in study area. The objective of the study was to evaluate the performance of ANMs in terms of client satisfaction in selected health care settings of North India. This cross-sectional study was conducted in two selected health care settings of North India. Material and Methods: Convenient sampling technique was used to select 7 ANMs and 100 clients from the study area. Data collection was done by using client satisfaction interview schedule. Descriptive and inferential statistics (χ2 test) was used. Results: Most (87%) clients were satisfied with the services provided by ANMs. The dissatisfaction in rural area was only 2% as compared to 24% in urban area. Lesser proportion of people were satisfied with family planning, provision of health services and other services. Conclusion: Clients in rural area were more satisfied as compared to clients in urban area .More satisfaction was reported in communication, maternal and child health and health education services.